Forensische Verfahren in den zeitgenössischen Künsten Forensic Architecture und andere Fallanalysen - Stuckey, Lisa (De Gruyter, 2022)
The research agency Forensic Architecture investigates war crimes and ecological as well as political crises and brings them into the exhibition as well as the courtroom through "Investigative Aesthetics" (MACBA 2017). Lisa Stuckey develops the figuration 'Law on Trial' to investigate why aesthetic and poetic forensic procedures are entrusted with a radical questioning of social justice; in selective excursuses, the study compares stratagems of Forensic Architecture with those of filmmaker Constanze Ruhm and poet M. NourbeSe Philip. After law became a "model for knowledge systems" (Vismann/Weitin 2006) in the 18th century, today's literal putting of law to the test is related to a new dimension of detection that follows the institutional critique of the 1990s and leads to a functional change of the arts.